Legal Recognition of Societal Organizations as Civil Society Representatives in Democratic Lawmaking - Purwanto, Argie Wahyu Wibawa; Uyun, Dhia Al; Zainudin, Arif (International Journal of Business, Law, and Education, 2026)
Public participation is an indispensable element of democratic lawmaking because it links statutory authority with social legitimacy. In Indonesia, societal organizations (organisasi kemasyarakatan, ormas) have a strategic position as intermediary institutions that aggregate collective interests and transmit them to state institutions. Although Law No. 12 of 2011 on Lawmaking, as amended most recently by Law No. 13 of 2022, recognizes public participation and introduces the language of meaningful participation, the statutory framework still does not expressly establish an enforceable obligation to involve societal organizations at each decisive stage of the legislative process. This article examines the legal consequences of that gap for democratic legitimacy, legislative accountability, and the quality of public control. Using normative legal research supported by statutory, conceptual, and comparative approaches, the article analyses Indonesian constitutional guarantees of association and expression, the legal functions of societal organizations under Law No. 17 of 2013, the doctrine of meaningful participation developed by the Constitutional Court, and selected comparative lessons from the Philippines. The study argues that the present Indonesian model remains vulnerable to procedural formalism because participation is frequently treated as access to consultation rather than as an institutionalized right to be heard, considered, and answered. The article recommends reformulating the Lawmaking Law by converting discretionary consultation clauses into mandatory provisions, establishing minimum procedural standards for consultation, requiring written feedback on civil society submissions, and creating a reviewable record of participation. Such reform would strengthen the rule of law by transforming societal organizations from occasional invitees into legally recognized partners in democratic legislation.